Happily ever after? Socioeconomic profiles in divorce cases during the first half of the 20th century, Buenos Aires province, Argentina - Valobra, Adriana María (2021)
Absolute divorce in Latin America has been studied, in particular, concerning those countries where its legal sanction was given early. However, not long ago, the inquiries about Argentina were rather exceptional. In general, they can be grouped into three lines: the analysis of political discourses and gender readings on the scope of the laws about marriage and the grounds for divorce; microhistory studies about the press and letters sent to the government that usually indicates that there was a divorce consensus among the population, although their statements override the possibilities of the sources and type of approach on them; and statistical studies that have made interesting contributions on the national scope, the geographic distribution and the difficulties that the series presents to reflect on other aspects. This work uses a series of data constructed from judicial sources to analyze the social profiles reconstructed in files that in 1955 entered as a divorce to the courts of the city of La Plata (province of Buenos Aires).